Specifying and implementing visual process modeling languages with DiaGen - Minas, Mark; Hoffmann, Berthold (Specifying and implementing visual process modeling languages with diagen, 2001)
This paper describes how a diagram language can be specified, based on graphs, graph grammars, and transformation rules, and how the diagram editor generator DIA GEN generates a diagram editor from such a specification. DIA GEN can be applied to practically every visual language, and to visual process modeling languages in particular. This is demonstrated with an editor and animator for statecharts. © 2001 Published by Elsevier Science B.V.
UnivIS-Import:2015-04-16:Pub.2001.tech.IMMD.IMMD2.spezif_3
Keywords: visual; process; modeling; language; diagen